Differences in eccentricity for sound-induced flash illusion in four visual fields. (January 2023) - Chang, Chun; Wang, Erlei; Yang, Jiajia; Luan, Xiaotong; Wang, Aijun; Zhang, Ming
A sound-induced flash illusion (SiFI) is a multisensory illusion dominated by auditory stimuli, in which the individual perceives that the number of visual flashes is equal to the number of auditory stimuli when visual flashes are presented along with an unequal number of auditory stimuli. Although the mechanisms underlying fission and fusion illusions have been documented, there is not yet a consensus on how they vary according to the different eccentricities. In the present study, by incorporating the classic SiFI paradigm into four different eccentricities, we aimed to investigate whether the SiFI varies under the different eccentricities. The results showed that the fission illusion varied significantly across the four eccentricities, with the perifovea (7°) and peripheral (11°) illusions being greater than the fovea and parafovea (3°) illusions. In contrast, the fusion illusion did not vary significantly across the four eccentricities. Our findings revealed that SiFI was affected by different visual fields and that there were differences between the fission and the fusion illusions. Furthermore, by examining the SiFI of eccentricity across visual fields, this study also suggests that bottom-up factors affect the SiFI.